2017
DOI: 10.18405/recfin20170107
|View full text |Cite
|
Sign up to set email alerts
|

Participação Feminina na Governança Corporativa de Empresas Familiares Listadas na BM&FBovespa

Abstract: RESUMOObjetivo: Este estudo objetiva analisar a presença das mulheres em níveis estratégicos da governança corporativa de empresas familiares listadas na BM&FBovespa. De modo específico busca: (i) identificar a composição do conselho de administração nas empresas familiares listadas na BM&FBovespa; (ii) caracterizar as empresas que possuem mulheres no conselho de administração; e, (iii) verificar quantas mulheres integram o conselho de administração proporcionalmente em cada empresa. Fundamento: As mulheres se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 2 publications
0
7
0
5
Order By: Relevance
“…Considering the presented background, this paper aims to identify how gender diversity affects the companies' performance, verifying the influence of the female participation, as directors and executives, on the accounting liquidity and risk of firms listed in the Brazilian Stock Exchange (B3). It is important to inform that Brazilian papers linking accounting, liquidity and gender diversity were not found; however, there are few studies related to gender and firm performance in the country, being possible to emphasize the papers of Silva and Margem (2015), Segura, Formigoni, Abreu, & Costa (2016), Vaccari and Beuren (2017) and Silva Júnior and Martins (2017).…”
mentioning
confidence: 99%
“…Considering the presented background, this paper aims to identify how gender diversity affects the companies' performance, verifying the influence of the female participation, as directors and executives, on the accounting liquidity and risk of firms listed in the Brazilian Stock Exchange (B3). It is important to inform that Brazilian papers linking accounting, liquidity and gender diversity were not found; however, there are few studies related to gender and firm performance in the country, being possible to emphasize the papers of Silva and Margem (2015), Segura, Formigoni, Abreu, & Costa (2016), Vaccari and Beuren (2017) and Silva Júnior and Martins (2017).…”
mentioning
confidence: 99%
“…Debates on gender issues have often raised the question of male dominance (Cruz et al, 2018;Estivalete et al, 2018;Silva & Martins, 2017;Vaccari & Beuren, 2017). In this study, female researchers were indeed found to be in quantitative disadvantage, with only 41.2% participation, matching the findings of Morais et al (2016), but not those of other authors focusing on specific areas in accounting (Luca et al, 2011).…”
Section: Discussionmentioning
confidence: 43%
“…Labor laws now exist which mandate gender equality in the workplace in terms of rights and work conditions, including parental leave (Vaccari & Beuren, 2017), but reconciling work and family is still a challenge for many women. According to Lazzarini et al (2018), in traditional societies women are conditioned to serve and care from childhood, while men are expected to focus on planning, decision making, problem solving and exploration of the outside world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations